Endotoxaemia and complement activation in acute pancreatitis in man. Issue 8 (August 1982) - Foulis, A K; Murray, W R; Galloway, D; McCartney, A C; Lang, E; Veitch, J; Whaley, K
Abstract : Twenty-four patients who experienced 26 attacks of acute pancreatitis were studied. Endotoxaemia, as measured by the limulus lysate assay, was present in 13 of the attacks. Six out of seven patients with systemic complications of the disease had endotoxaemia. C3 catabolism was increased in all 26 attacks of pancreatitis, and a falling level of C3 during attacks of severe pancreatitis was associated with a fatal outcome. There was statistical evidence of more complement activation in serum samples taken when patients had positive limulus lysate tests than when endotoxin was not detected in their blood.